Can the risk of coastal hazards be better communicated?. (March 2018) - Pile, Jeremy; Gouramanis, Chris; Switzer, Adam D.; Rush, Becky; Reynolds, Iain; Soria, Janneli Lea A.
Abstract: Destructive coastal hazards, including tsunami inundation and storm surges, periodically affect many of the world's coasts. To quantify the risk of such events and to identify premium levels for such hazards, the insurance industry commonly uses the available scientific literature, coupled with probabilistic modelling. Often, communicating the results of the modelling to clients is difficult, as it involves world or regional scale risk maps and complex statistics of recurrence intervals and exposure. Risk maps are particularly problematic because they necessarily generalise the information conveyed to the mapping scale, thereby reducing detail. As a result, entire coastlines can be labelled as "high risk", discouraging clients from investing, and/or leading to inappropriately high premium levels. This raises the question: What is the best way to communicate risk at a regional scale without broad generalisations? In our study, we have used historical events as case studies via the pedagogical premise of "Concept, Example, Consequence", and created a novel multifaceted poster map. Our approach will encourage reinsurance industry practitioners and clients to reconsider their communication of risk, re-evaluate localised risk, and provide a detailed alternative to the broad generalisations found in many products in the marketplace. Graphical abstract: fx1